2017
DOI: 10.1038/bmt.2016.312
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of bone loss and fractures in patients undergoing a hematopoietic stem cell transplant: a systematic review and meta-analysis

Abstract: The most effective method to prevent and treat bone loss following hematopoietic stem cell transplantation (HSCT) remains uncertain. We conducted a comprehensive search in four electronic databases until August 2015. We retrieved articles describing patients with bone loss or fractures who received HSCT. Controlled trials, with a follow-up period of at least 12 months, were included. Twelve studies (19 publications) met our inclusion criteria. A total of 643 participants underwent HSCT (85.7% allogeneic HSCT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…In summary, bisphosphonates generally prevented bone loss [98,101] or increased bone mass [97,102]. A metaanalysis confirmed that bisphosphonates, and in particular, zoledronic acid, are promising in the prevention of HSCTinduced bone loss [28].…”
Section: Bisphosphonatesmentioning
confidence: 83%
See 1 more Smart Citation
“…In summary, bisphosphonates generally prevented bone loss [98,101] or increased bone mass [97,102]. A metaanalysis confirmed that bisphosphonates, and in particular, zoledronic acid, are promising in the prevention of HSCTinduced bone loss [28].…”
Section: Bisphosphonatesmentioning
confidence: 83%
“…The relative risk was increased eightfold and seven-to ninefold, in women and men, respectively, compared with 45-to 64-year-old individuals from two population-based cohorts [26,27]. A substantial number of patients with multiple myeloma, who are known to be a risk of fracture independently of transplant, were included in this study [28]. The risk was higher in allogeneic than in autologous HSCT [27].…”
Section: Epidemiology Of Osteoporosis and Fracture In Adult Patients mentioning
confidence: 99%
“…103 Overall, bisphosphonates, in particular zoledronic acid, have been shown to be effective at preventing HCT-induced bone loss. 122 Currently, there is insufficient data to recommend one agent over the other, treatment frequency, or initiation timeframe. The appropriate duration of antiresorptive therapy is unclear and investigators have studied a treatment duration range between 3 and 60 months.…”
Section: Skeletal Complicationsmentioning
confidence: 99%
“…With improvements in stem cell transplant methodologies, long‐term survivorship has increased, but has brought with it attendant problems including increases in skeletal fragility and fracture risk, reflecting multiple factors including conditioning regimens, glucocorticoid use, deficits in nutritional support and often prolonged periods of hypogonadism . In addition to clinical risk factor assessment, the judicious use of anti‐resorptive therapies, particularly intravenous bisphosphonates, has been shown to limit bone loss, typically when provided at dosing schedules more intensive than those used for the treatment of osteoporosis . No clinical trials on the use of denosumab in patients undergoing bone marrow transplant have yet been reported.…”
Section: Haematologic Malignanciesmentioning
confidence: 99%